The Effect of Cognitive Behavioral Therapy on Knowledge of Fluid Intake Restrictions in Hemodialysis Patients - Hanifah, Siti; N Sukesi (International Journal of Contemporary Sciences (IJCS), 2024)
Hemodialysis is a treatment for patients with chronic kidney failure. The study investigated how cognitive behavioral therapy affects patients' understanding of fluid intake restrictions. The CKD patient fluid restriction compliance questionnaire was tested. The study involved 20 valid questionnaires. The validity test produced 0.514, while the reliability test produced a result of 0.70, indicating that the data was very consistent with an alpha value of >0.6. The pre-experimental design with a One Group Pretest Posttest design with 60 participants. Before therapy, 35 (58.3%) were non-compliant, 17 (28.3%) were somewhat compliant, 8 (13.3%) were compliant. After therapy, 3 (5%) were non-compliant, 11 (18.3%) were somewhat compliant, and 46 (76.7%) were compliant. The results of the Wilcoxon Test p value of 0.000, indicating that there was an effect of cognitive behavioral therapy on knowledge of fluid intake restrictions.